The role of school leaders in promoting community partnership / Thikryat Jibril Qaralleh - Qaralleh, Thikryat Jibril (Universiti Teknologi MARA, 2021)
This study is an attempt to identify the role of school leaders in promoting community partnership (CP) in public schools providing general education in Al-Kharj Governorate, Saudi Arabia, and exploring the ways to develop this type of relationship. For this purpose, a descriptive research method was utilized, recruiting 5,320 teachers of both genders as the study population. The results indicated the moderate role of school leaders in boosting CP in these public schools in Al-Kharj Governorate in Saudi Arabia. Overall, the respondents demonstrated a moderate level of appreciation. As well, the leaders had the visions to expand CP by involving the community in educational development processes. It was also recommended to increase the levels of participation by placing the community in the management of local public schools. The findings further implied that school leaders needed to form committees by engaging the community members therein in order to strengthen the educational process.